(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Background: Establishing individuality is an imperative aspect of any investigative procedure. Sex and age determination in Forensic Odontology is the application of dental principles for legal issues in crimes like theft, sexual assault, murder etc. Aim: correlate the Cytoplasmic area, nuclear area, N/C ratio for estimation of age and sex of an individual as an adjunction forensic(crime) investigation in the Lucknow population. Methodology: In this study, 100 labial smears were collected from normal individuals, dividing them into four age groups. (Group1:20-30,Group2:30- 40,Group3:40-50,Group4:50-60).The collected smear samples were stained using Papanicolaou stain. The average sizes of the cells and nucleus were measured using image proplus image analysis software. Result: N/C ratio, NA and CA were more in females when compared to males. All the above parameters reduced with progressing age in both the sexes. All parameters showed statistically significant difference in different age groups. Conclusion: Cytomorphometric evaluation of exfoliated oral cells proves reliable tool for correlation of age.